Effects of pomegranate juice consumption on sperm quality, spermatogenic cell density, antioxidant activity and testosterone level in male rats - Türk, G; Sönmez, M; Aydın, M; Yüce, A; Gür, S; Yüksel, M; Aksu, Eh; Aksoy, H (My University, 2008)
Background & aim: Pomegranate fruit is inescapably linked with fertility, birth and eternal life because of its many seeds. The aim of this study was to investigate the effects of pomegranate juice (PJ) consumption on sperm quality, spermatogenic cell density, antioxidant activity and testosterone level of male healthy rats. Methods: Twenty-eight healthy adult male Wistar rats were divided into four groups; each group containing seven rats. One milliliter distilled water, 0.25 mL PJ plus 0.75 mL distilled water, 0.50 mL PJ plus 0.50 mL distilled water and 1 mL PJ were given daily for seven weeks by gavage to rats in the first, second, third and fourth groups, respectively. Body and reproductive organ weights, spermatogenic cell density, sperm characteristics, levels of antioxidant vitamins, testosterone, and lipid peroxidation and, antioxidant enzyme activities were investigated. All analyses were done only once at the end of the seven week study period. Data were compared by analysis of variance (ANOVA) and the degree of significance was set at P < 0.05. Results: A significant decrease in malondialdehyde (MDA) level and marked increases in glutathione (GSH), glutathione peroxidase (GSH-Px) and catalase (CAT) activities, and vitamin C level were observed in rats treated with different doses of PJ. PJ consumption provided an increase in epididymal sperm concentration, sperm motility, spermatogenic cell density and diameter of seminiferous tubules and germinal cell layer thickness, and it decreased abnormal sperm rate when compared to the control group. Conclusion: The results suggest that PJ consumption improves sperm quality and antioxidant activity of rats.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Pomegranate juice Spermatogenic cell density Sperm characteristics Testosterone Lipid peroxidation Antioxidant enzymes